PENGARUH SUASANA TOKO DAN LOKASI TOKO TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO BUKU ZANAFA PEKANBARU - Putri Wulandari; Okta Karneli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted at the Zanafa Pekanbaru Bookstore located at JL. HR. Subrantas metropolitan city complex (MTC) / Giant Block A 39-40 Handsome Pekanbaru Riau. The problem in this study is the achievement of the company's target where it never reaches the target of 100% and always experiences a decline in achieving sales targets at the Zanafa Pekanbaru Bookstore. The purpose of this study was to determine the effect of shop atmosphere and store location on purchasing decisions at the Zanafa Pekanbaru bookstore. In this study the method used was quantitative descriptive with the SPSS program. The research samples were 100 people from a population of 60,428 obtained from calculation of Slovin formula. Data obtained from the results of the questionnaire were then processed and then tested through the SPSS 24 program. The testing of multiple linear regression analysis from this study was Y = 2.695 + 0.108X1 + 0.253X2. The research that has been done shows that the respondent's response to the store atmosphere and location of the store is in a good category while in the purchasing decision the category is quite good. While the t test that has been done shows that the variable store atmosphere and store location partially have a significant effect on purchasing decisions. The f test results show that simultaneously the store atmosphere and store location have a significant effect on purchasing decisions. While the calculation of the coefficient of determination (R2) obtained values obtained R2 (Rsquare) of 0.495 or 49.5%. This shows that the percentage contribution to the influence of the store atmosphere and store location on consumer purchasing decisions is 49.5%. While the remaining percentage which is equal to 50.5% is influenced by other variables not included in this research variable.  Keywords: Store Atmosphere, Store Location, Purchase Decision